DETERMINAN UTILISASI LAYANAN WISATA KEBUGARAN (WELLNESS TOURISM) DI RSUP DR. SARDJITO, YOGYAKARTA - Firman, Firman; Lestari, Kartika; Garnet, Citra Corneriski (UI Scholars Hub, 2024)
Wellness tourism have become a new trend for Indonesian people in maintaining their physical and spiritual health. Dr. Sardjito General Central Hospital is one of the hospital institutions that develops medical & wellness tourism services by utilizing Javanese culture and using traditional materials. This study aims to determine the factors that influence patients using wellness tourism. Qualitative research with a phenomenological approach and sample selection using purposive sampling with specified criteria. The total informants were 10 patients, and 5 from service providers such as management, administration and therapists at the Kalimosodo polyclinic. Data collection was carried out through in-depth interviews and thematic analysis. The characteristics of patients using medical and wellness tourism services are women with a high educational background. The determinants of using fitness services at Dr. Sardjito Hospital are that the patient knows the function of the fitness service, the facilities are considered clean and adequate, the service costs are affordable, and the patient also has family support. This study showed that predisposing factors or the patient's personal condition are the dominant factors in utilizing fitness services. The use of Dr. Sardjito Hospital fitness services is influenced by individual characteristics, knowledge and positive perceptions of facilities and quality services. Thus, hospital management needs to increase literacy regarding the benefits of fitness services for patients so that this service becomes increasingly popular and becomes an attractive service option for patients and the public to stay healthy and productive.